From bottom to top: the entire distribution of market income in Germany, 1992 - 2001 - Stefan Bach; Giacomo Corneo; Viktor Steiner (Institute for the Study of Labor (IZA), 2007)
We analyze the distribution and concentration of market incomes in Germany in the period 1992 to 2001 on the basis of an integrated data set of individual tax returns and the German Socio-Economic Panel. The unique feature of this integrated data set is that it encompasses the whole spectrum of the population, from the very poor to the very rich. We find a modest increase in overall inequality of market incomes as measured by the Gini coefficient. However, we also document a substantial drop of median income and a remarkable income growth at the top 0.1% of the income distribution. The increase of income inequality was stronger in East Germany than in West Germany. In both regions, the income concentration process strongly benefited the economic elite, which we define as the richest 0.001% persons in the population. While the elite mainly obtains its income from business and capital, the income share that it receives in form of wage income is increasing.
urn:nbn:de:101:1-20080402516
Keywords: 330; Lohnstruktur; Einkommensverteilung; Wirtschaftswachstum; Deutschland